Modeling and Control of the tPVTOL∗. Issue 9 (2015) - Villagómez, J.G.; Vargas, M.; Ortega, M.G.; Rubio, F.R.
Abstract: This paper presents the modeling and control of a planar multibody aerial platform, composed of a Miniature Vertical Take-Off and Landing Aerial Platform (MAV-VTOL) and a camera positioning system. The goal is to improve the current operational profile of visual sensors onboard the MAV, by broadening current aerial configurations for visual sensors tasks with novel capabilities to disengage the dynamic coupling due to typical setups. The Newton-Euler and Euler-Lagrange formalisms are simultaneously applied aiming at obtain and verify coupling terms between the aerial and the camera positioning system. Results of linear and nonlinear control techniques applied to control the position and orientation of the camera frame onboard the MAV are presented.